The Analysis of Social Class Conflict in Ruben Ostlund’s Triangle of Sadness (2022): In Sociolinguistic Context (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2026)
This research aims to analyze how social class conflict is represented in the film through dialogues, interactions, and language practices. The study applies a qualitative descriptive method using Marxist theory supported by a sociolinguistic perspective. The primary data consist of selected dialogues and scenes from the fashion industry setting, the luxury yacht, and the island scenario. The findings reveal that social class conflict is represented not only through economic ownership, but also through speech patterns, commands, responses, and linguistic strategies used to maintain social positions. In elite environments, language functions as a symbol of exclusivity and social status. On the luxury yacht, hierarchical relations are maintained through institutionalized politeness and obedience. In the island scenario, power shifts when control over essential resources and survival skills replaces economic wealth as the basis of authority. In conclusion, the film portrays social class conflict as dynamic and context-dependent. Language functions as an instrument for constructing, sustaining, and negotiating social hierarchy. Ultimately, the film exposes the instability of class structures under capitalism, revealing that class power is not absolute, but contingent upon control over material resources and social recognition.